Investigación periodística para la difusión de información en los medios radiales: dinastía 107.1 y la voz de El Oro 1310 AM del cantón Pasaje, provincia de El Oro, período 2014. - Procel Guayara, Luis Ángel (2015)
Radio is today the means of conventional communication wider acceptance and coverage among the inhabitants of the country, its portability and ease make this never go out of fashion, but it is no less certain that in terms of quality programming, this still leaves much to be desired. Perhaps through ignorance or simple oversight, many of the existing stations are limited to reading newspapers in their news to put filler music and create a senseless another program, many radios lack of production equipment, style manuals or any planning that allows them to improve the quality of its information products. This is the case of radio Dynasty and Voice of Gold, both located in canton Pasaje El Oro province, same as lacking a guide in carrying out their journalistic activities.